2014
DOI: 10.1080/03650340.2014.956660
|View full text |Cite
|
Sign up to set email alerts
|

Physical indicators of soil erosion, aggregate stability and erodibility

Abstract: The sustained interest in soil erosion research is an indication of both its importance and the lack of definite solutions that can halt its negative impacts on the environment. This study reviewed the literature on trends, new perspectives, gaps and conflicts in soil erosion studies in the South African context. The suitability of using the relationship between aggregate stability and interrill erodibility as a predictor of the soil susceptibility to erosion was also investigated. This relationship is often u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 57 publications
2
18
1
Order By: Relevance
“…Soil aggregate size and stability are also used to characterize soil structure because those indicators are correlated with several soil functions, including gas exchange and C sequestration through physical protection of soil organic matter (SOM) [4]. Aggregate stability (AS) provides a good indicator of soil erosion potential since reduced AS increases susceptibility to crusting and runoff while also reducing soil permeability to air, water and roots [7,8]. A third key indicator of soil structure is penetration resistance (PR) which is directly correlated with root growth [9].…”
Section: Introductionmentioning
confidence: 99%
“…Soil aggregate size and stability are also used to characterize soil structure because those indicators are correlated with several soil functions, including gas exchange and C sequestration through physical protection of soil organic matter (SOM) [4]. Aggregate stability (AS) provides a good indicator of soil erosion potential since reduced AS increases susceptibility to crusting and runoff while also reducing soil permeability to air, water and roots [7,8]. A third key indicator of soil structure is penetration resistance (PR) which is directly correlated with root growth [9].…”
Section: Introductionmentioning
confidence: 99%
“…Use of AS as an erodibility index however has shown complex behaviour (Bryan, 2000). Previous research revealed that its performance varied between soils (non-cohesive versus cohesive), between rainfall events (impact of previous rainstorms and crusting, re-establishment of coherence after tillage), and by particular erosion processes at stake (splash versus rill erosion) ( Barthès and Roose, 2002;Materechera, 2009;Nciizah and Wakindiki, 2015;Ding and Zhang, 2016). The use of various disruptive forces to assess AS, forces that may or may not correspond to field conditions (Almajmaie et al, 2017a(Almajmaie et al, , 2017b adds to this complexity.…”
Section: Introductionmentioning
confidence: 99%
“…The soils were classified according to USDA Soil Taxonomy (Soil Survey Staff, 2014) and World Reference Base (WRB) for soil resources (FAO, 2014). The classifications were correlated with the local series classification of soils (Moss, 1957).…”
Section: Laboratory Analysis and Soil Classificationmentioning
confidence: 99%
“…Though in arable cropping, more emphasis is placed on the surface texture as it influences workability, nutrient and water retention, the subsurface texture is of much importance with respect to nutrient adsorption, water infiltration and susceptibility to leaching. Soil texture therefore influences the soil's inherent fertility and directly or indirectly, erodibility and moisture characteristics which could have great impacts on soil management, rooting ability and crop yields (Jalota et al, 2010;Nciizah and Wakindiki, 2015). The chemical properties revealed that a available P is generally deficient as none of the pedons contains the required critical level of 15 mg/kg (Fernandes and Soratto, 2012) for sustainable arable cropping.…”
Section: Soil Classification and Land Characteristicsmentioning
confidence: 99%